The microbial signature of drinking waters: myth or reality? - Harmand, J.; Paulou, L.; Desmoutiers, J.; Garrelly, L; Dabert, P.; Godon, J.J. (Water science and technology, 2006)
This paper presents a new software developed for analyzing single strand conformation polymorphism (SSCP) electrophoresis patterns delivered by the genetic analyzer ABI310 (Applied Biosystems). SSCP is a molecular typing technique based on the PCR amplification of microbial 16S rDNA and used for the monitoring of complex microbial ecosystems dynamics. The software – a home-made MATLAB toolbox called MODIMECO – developed for the analysis of SSCP patterns is presented. MODIMECO includes a number of basic signal processing abilities as well as largely used statistical tools such as the well known principal component analysis. The use of the SSCP for assessing the hypothesis of the existence of a microbial signature of drinking waters illustrates the typical advantages of using such software tools. Results are discussed and conclusions drawn.